(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article aims at analyzing the current process of birth’s medicalization starting from the observation of the position of woman in labour as a proof of the medical approach to gestation and pregnancy. This research traces the historical origin of the birth’s medicalization from the XVII century when the male doctor appeared and replaced the midwives, thus breaking the traditional exclusiveness of women on the birth scene. Looking at the state-of-the-art in Italy, this paper highlights the frequent risks of excessive medicalization, through a comparison of the methods of hospital assistance in different geographical areas.